Bunsoy - Gojo Cruz, Genaro R.; Kempis, Leo; Tamayo, Faith (Quezon City LG & M Corporation, 2013)
"Bunsoy answers the questions many children ask today about their parents who need to work abroad."
"Ages 3-6 y.o."
Text in English and Filipino.
Keywords: Children of foreign workers -- Philippines -- Juvenile literature; Children's stories, Philippine (English)